INVESTIGATING THE PROBLEM OF STUDENTS’ LOW SCORE IN READING SECTION AT TOEFL CLASS - Torikin Torikin; Muhammad Yunus; Mutmainnah Mustofa; Sonny Elfiyanto (Language-Edu, 2022)
The main focus of this research is to investigate the students’ ability in English as a second of foreign language in the reading section. The subject of this study was ten students of Kanzun Najah Batu. The research was a survey qualitative. The data collection technique was a questionnaire survey via Google Sheets and in-depth interview techniques recorded face-to-face using smartphones. Ten students participated in the questionnaire survey and five students participated in the in-depth interviews. Analyze and interpret data through qualitative procedures. The study focused on finding out the difficulties students face when answering TOEFL questions in the reading section. The study was limited to the difficulties faced by Kanzun Najah Batu students who had previously taken the test of TOEFL for any purpose of answering the TOEFL test. The findings of this study are the difficulties students face in answering TOEFL test questions in the reading section, mainly due to a lack of basic skills, less practice, less motivation, and individual differences among students.Keywords: TOEFL, Reading